Verificação da adequabilidade do método BioTRIZ na aplicação da biomimética no ensino de projeto de arquitetura - Cunha, Ronnie Elder da (2015)
Despite the fact that biomimicry has been widely used in the fields of design and engineering, its application methods in architectural design are not yet clear, especially in the architectural design education. The transfer of a concept or mechanism of a living organism for non-living systems is not a trivial task and requires knowledge between two domains, the biological and the design. The BioTRIZ, a systematic method and especially developed based on biological phenomena, does not require deep understanding about natural organisms. This study aimed at verifying the adequability of BioTRIZ method in the application of biomimetic concepts in atelier design teaching in the early periods of the architecture program. Exploratory case studies was used through design exercises in models atelier classes with the 3rd semester students of the Architecture and Urban Planning Program of the Federal University of Paraiba. The work proceedings were divided into eight steps: variables definition, pilot studies, teams training, data collection in design exercises with application of BioTRIZ method, questionnaires, focus groups sessions, data analysis and results discussion. It was concluded that BioTRIZ method was not entirely suitable for design education in models atelier, due to the limited design repertoire of students, the difficulties in avoiding fixation on predefined ideas and limitations in the ability to transform specific features in abstract ones and vice versa, all those being requirements for effective use of BioTRIZ method.